O território em disputa: territorialidades, redes sociais e grupos políticos de Ivaiporã/PR (2000/2012) - Denez, Cleiton Costa (2016)
This research was carried out from the need to understand how the political groups are organized in the territory and which strategies are used to carry on the political power in a such territory as the municipality of Ivaiporã/PR. The hypothesis is that to ensure control over certain territory the power groups use territorialities to legitimate the practice of power. To organize themselves into groups the political parties produce networks that are organized around a common goal. For this purpose we used discourse analysis to identify the ideologies and identities to legitimate the ensure of power and analysis of social networks to link different actors and the creation and content of power groups. With the identification of the political groups in Ivaiporã was possible to verify the presence of three main political forces. Each political group, produces a specific territoriality to convince the electorate segments of why it should be chosen. What territorialities the three political forces produced in the period of 2000-2012 to convince the voters why they should rule Ivaiporã. For Pedro Papin (PSDB) free public transportation and customer service to the people are the reason. For Professor Cyro (PT) the reason is the need for renew of political practices in Ivaiporã with an honest municipal government. Carlos Gil (PMDB) Ivaiporã needs development and progress, with a dynamic local government. So to come to power, each political group produces an identity in the territory of Ivaiporã where portions of the population identify themselves with one or the other, territoriality to reach the most support and voters who identify themselves with the same, derives its entitlement to ensure the power and produce the territory according to the balance of power established between the different parties and political groups present